SDG16 - Peace and Justice : Challenges, Actions and the Way Forward - Radović, Vesela (Concise guides to the United Nations Sustainable Development Goals ;, 2019)
This book details how interested parties can, must and are getting ahead of the curve to promote peace, provide access to justice and build accountable institutions for all. It envisions a hopeful future in which the impacts of SDG16 are likely to be far more positive, transformational, and visible much more quickly, than we might have imagined.